Is Enterprise Bargaining Still a Better Way of Working? - Townsend, K.; Wilkinson, A.; Burgess, John (Sage Journals, 2013)
In 1989, the Business Council of Australia (BCA) produced a blueprint for change titled ‘Enterprise based bargaining units: A better way of working’. To a great extent, this document and the corresponding shifts in business, government and union approaches to wage and conditions determination meant that Australia shifted from a centralised to a workplace system of bargaining. After more than two decades of enterprise bargaining, though, we ask the question: Is it still a better way of working? While the Business Council of Australia pointed to a panoply of advantages, we look at the other side of the argument. Decentralisation may be inefficient at a number of levels. First, there is the procedure of bargaining and the resources, expertise and time that is required. Second, there are the outcomes of bargaining, where despite a more individual focus, in many cases, outcomes demonstrate very little variation across enterprises. Finally, there are the collateral consequences of bargaining: conflict, reduced trust and disruption. Is enterprise bargaining still meeting the needs of the actors or has the model run its course? We consider two case studies of bargaining that demonstrate the limitations and advantages of enterprise bargaining.